Can peritoneal dialysis be used in preterm infants with congenital diaphragmatic hernia? - MEMİŞOĞLU, ASLI; ALPAY, HARİKA; YILDIZ, NURDAN (INFORMA HEALTHCARE, 2013)
Peritoneal dialysis (PD) is considered as the most common form of renal replacement therapy for newborns including preterms with acute kidney injury (AKI). Although there are several reports describing successful PD performed for AKI in preterm infants, there is no data describing the use of PD to treat AKI in preterm newborns with congenital diaphragmatic hernia (CDH), which is one of the contraindications for PD. We present a preterm newborn with CDH, truncus arteriosus and AKI treated with PD and emphasize that PD may be successfully performed with caution even in cases of contraindications when other renal replacement therapies cannot be used.
Keywords: Acute kidney injury; congenital diaphragmatic hernia; peritoneal dialysis; preterm; ACUTE-RENAL-FAILURE; NEWBORNS